Intrigues of biofilm: A perspective in veterinary medicine - Umar Faruk, Abdullahi; Ephraim, Igwenagu; Anas, Mu’azu (Veterinary World, 2016)
Biofilm has a tremendous impact in the field of veterinary medicine, especially the livestock industry, leading to a serious economic loss. Over the years, little attention has been given to biofilm in animals with most of the research geared toward human biofilm diseases. The greatest challenge posed by biofilm is in its incredible ability to resist most of the currently existing antibiotics. This mystery can best be demystified through understanding the mechanism of the quorum sensing which regulate the pathophysiology of biofilm. Ability of biofilm formation in a variety of inanimate surfaces such as animal food contact surfaces is responsible for a host of biofilm diseases affecting animals and humans. In this review, we highlighted some of the challenges of biofilm in livestock and food industries. Also highlighted are; mechanisms of biofilm development, best diagnostic approach and possible novel therapeutic measures needed to combat the menace of biofilm in veterinary medicine.